Japan in the Year 2000 : (The Japan times, 1983)
Population Aging in Japan: Problems and Policy Issues in 21st Century. International Case of Japan." Prepared for the International Conference on Population and Family Planning, Japan in the Year 2000. Preparing Japan for an Age of Internationalization, the Aging Society and Maturity.